Effects of Abiotic Factors on Acetylene Reduction by Cyanobacteria Epiphytic on Moss at a Subantarctic Island - Smith, Valdon R. (1984)
Acetylene reduction (AR) rates by cyanobacteria epiphytic on a moss at Marion Island (46°54′ S, 37°45′ E) increased from −5°C to a maximum at 25 to 27°C. Q(10) values between 0 and 25°C were between 2.3 and 2.9, depending on photosynthetic photon flux density. AR rates declined sharply at temperatures above the optimum and were lower at 35°C than at 0°C. Photosynthetic photon flux density at low levels markedly influenced AR, and half of the maximum rate occurred at 84 μmol m(−2) s(−1), saturation occurring at ca. 1,000 μmol m(−2) s(−1). Higher photosynthetic photon flux density levels decreased AR rates. AR increased up to the highest sample moisture content investigated (3,405%), and the pH optimum was between 5.9 and 6.2. The addition of P, Co, and Mo, individually or together, depressed AR.